Women in the World of the Earliest Christians Illuminating Ancient Ways of life - Cohick, Lynn H. (Grand Rapids,Michigan Baker Academic, 2009)
Draws on first-century Jewish and Greco-Roman documents to examine the lives and experiences of the earliest Christian women.
Keywords: Christian women -- Rome -- Social life and customs. Jewish women -- Rome -- Social life and customs. Women -- Rome -- Social life and customs